“Distribution of dominant wavelengths predicts jackdaw (Corvus monedula) color discrimination performance” - Lingstädt, Farina; Apostel, Aylin; Rose, Jonas (Frontiers in Physiology, 2025)
Color vision is an important perceptual ability in most species and a crucial capacity underlying any cognitive task working with color stimuli. Birds are known for their outstanding vision and tetrachromacy. Two jackdaws were trained to indicate whether they perceive two colors as same or different. The dominant wavelengths of the experimental colors were assessed to relate the birds’ performance to the physical qualities of the stimuli. The results indicate that the differences or similarities in dominant wavelengths of the colors had a strong influence on the behavioral data. Colors related to a reduced discriminatory performance were colors of particularly close wavelengths, whereas differences in saturation or brightness were less relevant. Overall, jackdaws mostly relied on hue to discriminate color pairs, and their behavior strongly reflected the physical composition of the color set. These findings show that when working with color stimuli, not only the perceptual abilities of the particular species, but also the technical aspects concerning the color presentation have to be considered carefully.